(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The creation and use of the source material at the initial stage of breeding work is an important factor in increasing its effectiveness. Cultured and wild plant forms are used as the starting material in breeding. The following main types and methods of obtaining the starting material are used in wheat breeding: natural and hybrid populations, as well as artificial mutations and polyploid forms. The use of intraspecific and remote hybridization in the breeding work of the Department of wheat breeding and primary seed production allowed to obtain the original source material from which, by individual selection, varieties were created that were approved for use on the territory of the Kyrgyz Republic.